Computational intelligence based power system security assessment and improvement under multi- contingencies conditions / Nor Rul Hasma Abdullah - Abdullah, Nor Rul Hasma (Institute of Graduate Studies, UiTM, 2012)
This thesis presents new techniques for voltage stability assessment and improvement in power system under multi-contingencies. A line-based voltage stability index termed as Static Voltage Stability Index (SVSI) was used to evaluate the voltage stability condition on a line. The value of SVSI was computed to identify the most sensitive line and corresponding weak bus in the system.